A Focus Group Study Among Inactive Adults Regarding the Perceptions of a Theory-Based Physical Activity App - Nibbeling, Nicky; Simons, Monique; Sporrel, Karlijn; Deutekom, Marije (Frontiers in Public Health, 2021)
Background: Despite the increasing attention for the positive effects of physical activity (PA) nearly half of the Dutch citizens does not meet the national PA guidelines. A promising method for increasing PA of inactive individuals are mobile exercise applications (apps). The Playful Active data-driven Urban Living (PAUL) application is a smartphone-based app developed to motivate healthy inactive urban residents to become more physically active in public urban spaces. The persuasive strategies included in the app are derived from health behavior change theories. However, these theories do not inform how to operationalize the strategies into an app. This study aims to explore preferences regarding implementation types and design characteristics of these strategies. Objective: The purpose of this study was to get insight in the needs, wishes and preferences regarding the practical operationalization of persuasive strategies in a mobile application aimed at promoting PA in healthy inactive adults. Methods: Five semi-structured focus groups were performed to collect data from twenty-five inactive healthy adults living in Amsterdam, The Netherlands. During the focus groups, participants were led into a discussion about six predefined theory-based persuasive strategies (e.g. self-monitoring, feedback, goal-setting, reminders, rewards & social support) directed by two moderators. The audio-recorded focus groups were transcribed verbatim and analyzed following the framework approach. Results: Participants were aged between 35 and 55 years (mean age 49.2). Outcomes demonstrated diverse preferences for implementation types and design characteristics of persuasive strategies in mobile applications. Basic statistics (such as distance, time and calories), positive feedback based on easy-to-achieve goals that relate to health guidelines and motivating reminders on a relevant moment were preferred. Participants had mixed preferences regarding rewards and a social platform to invite other users to join PA. Conclusions: Results indicated that preferences differed between people, showing a need for an app that is personalized and can be adapted based on these personal preferences. Functions (such as goal setting, reminders & feedback) related to health guidelines were preferred by the participants in order to motivate them to increase PA. Developers of exercise interventions should therefore take such functions into account.